2012
DOI: 10.1177/0269881112456611
|View full text |Cite
|
Sign up to set email alerts
|

Durability of improvement in post-traumatic stress disorder symptoms and absence of harmful effects or drug dependency after 3,4-methylenedioxymethamphetamine-assisted psychotherapy: a prospective long-term follow-up study

Abstract: We report follow-up data evaluating the long-term outcomes for the first completed trial of 3,4-methylenedioxymethamphetamine (MDMA)-assisted psychotherapy for chronic, treatment-resistant post-traumatic stress disorder (PTSD) (Mithoefer et al., 2011). All of the 19 subjects who received MDMA-assisted treatment in the original trial participated in the long-term follow-up (LTFU), with 16 out of 19 completing all of the long-term outcome measures, which were administered from 17 to 74 months after the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
275
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(296 citation statements)
references
References 83 publications
(96 reference statements)
14
275
0
7
Order By: Relevance
“…This pattern of effects provides further evidence that the drug may be useful in the treatment of PTSD, by facilitating engagement with the therapist and increasing the client's ability to focus on negative emotions (Mithoefer et al, 2013). By contrast, intranasal oxytocin produced small increases in selected ratings of sociability and enhanced negative emotion recognition.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This pattern of effects provides further evidence that the drug may be useful in the treatment of PTSD, by facilitating engagement with the therapist and increasing the client's ability to focus on negative emotions (Mithoefer et al, 2013). By contrast, intranasal oxytocin produced small increases in selected ratings of sociability and enhanced negative emotion recognition.…”
Section: Discussionmentioning
confidence: 73%
“…Nonetheless, the extent to which MDMA increases social behavior by decreasing sensitivity to negative expressions or increasing sensitivity to positive expressions remains to be resolved. In a recent study, patients receiving MDMAassisted treatment for PTSD (Mithoefer et al, 2013) reported an increased ability to focus on negative emotions. However, the nature of the MDMA effect remains unclear.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The first randomized controlled trials (RCTs) of MDMAassisted psychotherapy for treatment-resistant PTSD demonstrated decreases in both clinician-and participant-rated symptom severity (Mithoefer et al, 2011;Oehen et al, 2013). The efficacy of these interventions persisted at follow-up (Mithoefer et al, 2012), and effect sizes surpassed even those demonstrated by prolonged exposure therapy, the most widely accepted treatment for PTSD (Amoroso and Workman, 2016). Nonetheless, limitations pertaining to modest sample sizes and potential implicit biases warrant cautious interpretation of these preliminary, yet promising results.…”
Section: Introductionmentioning
confidence: 99%
“…Variability in temperature responses may explain the large individual differences in the emergence of adverse psychological and cognitive symptoms seen in some longterm MDMA users (for review, see Parrott, 2013b). Therefore, despite the modest hyperthermic responses to MDMA seen in humans under standard laboratory conditions (Freedman et al, 2005;Liechti, 2014), and its potential as a therapeutic agent for post-traumatic stress disorder (Mithoefer et al, 2011(Mithoefer et al, , 2013, our study underscores the possible dangers of 'recreational' MDMA use.…”
Section: Conclusion and Translational Relevancementioning
confidence: 72%